Scoping review on the genotoxicity of silver nanoparticles in endodontics: therapeutic saviors or genetic saboteurs? - Lin, Galvin Sim Siang; Lestari, Widya; Muhamad Halil, Mohd Haikal; Abd Aziz, Mohd Syafiq (Springer Nature, 2024)
Silver nanoparticles (AgNPs) have gained prominence in endodontics due to their exceptional antimicrobial properties. However, concerns regarding their genotoxic potential have prompted investigations into their safety profiles. This scoping review aims to consolidate current knowledge on the genotoxic effects of AgNPs in the field of endodontics. A thorough literature search across seven electronic databases was conducted using specific keywords. Inclusion criteria included experimental studies published in English from January 1960 to March 2024, addressing the genotoxicity of AgNPs in endodontic applications. Study selection and data extraction were conducted independently. The Quality Assessment Tool For In Vitro Studies (QUIN) tool was employed to evaluate the risk of bias in each study. 5 articles were selected, of which 3 were in vitro experimental designs, while the remaining were ex vivo studies. All were published between 2009 and 2021. AgNPs have been used as root canal irrigating solutions, pulp-capping materials, and root canal sealers. Most studies employed the comet assay for genotoxic evaluation. One study was found to have a low risk of bias, while others were categorized as having a medium risk. Mixed findings were noted on the genotoxic effects of AgNPs using various assays. The genotoxic potential of AgNPs somewhat poses concerns for endodontic practices. This review highlights the need for further research to develop safer alternatives and optimize their concentrations and exposure durations.